Analisis Pemberdayaan UMKM Melalui Filantropi Zakat Dalam Mewujudkan SDGs (Sustainable Development Goals) - Salsabila Putri; Sri Sudiarti; Rahmat Daim Harahap (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
MSMEs are one of the driving wheels of the economy that has the potential to realize the SDGs goals, namely without poverty and hunger. One that plays a role in realizing the SDGs by reducing the poverty rate is zakat. The purpose of this research in general is to realize sustainable development through empowering MSMEs. The research method used is qualitative with triangulation analysis techniques. The results of this study are that MSMEs can benefit from empowering productive zakat MSMEs provided by LAZ, which assistance can help develop their businesses and help prosper the family economy. This is one of the efforts that can be said to be successful in realizing one of the goals of sustainable development, namely without poverty and hunger Keywords: MSME, Zakat, SDGs